Applying Metacognitive Strategies in Comprehending English Reading Texts - Zulfadli A. Aziz; Chairina Nasir; Ramazani Ramazani (Soegijapranata Catholic University, 2019)
Comprehending English text is still regarded as hard for students. Metacognitive strategies have been considered effective in overcoming reading difficulties by many researchers. The objective of this study is to describe the application of three types of metacognitive reading strategies (global strategies, problem solving strategies, and support strategies) used by the students of Senior High School (SMAN) 1 Ingin Jaya, Aceh Besar. It is a descriptive qualitative study. Metacognitive Awareness of Reading Strategies Inventory (MARSI) questionnaire suggested by Mokhtari and Reichard (2002) was used to collect the data. The result of the study revealed that the students generally showed moderate awareness of all strategies and held a preference of using Problem Solving Strategies, followed by Support Strategies and Global Strategies respectively. The study also showed that high performance students used the strategies more frequently than low performance students. It can be concluded that the more students aware of using metacognitive reading strategies, the better their performance is in reading skill. Therefore, teaching the students to use metacognitive strategies can be a solution in enhancing students’ reading ability.